The Influence of Islamic Branding and Religiosity on Brand Image - Anggie Lia Andini; Popy Rufaidah (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2017)
The purpose of this study is to identify the magnitude of influence of Islamic branding and religiosity on brand image. Problem formulations in this research are whether there is an influence of Islamic branding and religiosity on brand image. This study uses explanatory survey method to explain the causal relationship of research variables through hypothesis testing. The population of the study is the consumers of cosmetic products in Indonesia. The study uses purpose sampling method, targeting the consumers of halal cosmetics and Islamic brands. Validity test results show that out of 37 question items, 36 items have correlation scores above 0.30 which means good and valid at 1% of significance level. Reliability test results show that all variables have Alpha Cronbach scores above 0.90 which means very reliable and significant at 1% of significance level. The study results show that Islamic branding and religiosity have significant influence on brand image. Islamic branding has a greater than toward brand image.Keywords: Brand Image, Islamic Branding, and Religiosity